2018
DOI: 10.1007/s00253-018-9005-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MALDI-TOF mass spectrometry for the competitiveness analysis of selected indigenous cowpea (Vigna unguiculata L. Walp.) Bradyrhizobium strains from Kenya

Abstract: Cowpea N fixation and yield can be enhanced by selecting competitive and efficient indigenous rhizobia. Strains from contrasting agro-ecologies of Kilifi and Mbeere (Kenya) were screened. Two pot experiments were established consisting of 13 Bradyrhizobium strains; experiment 1 (11 Mbeere + CBA + BK1 from Burkina Faso), experiment 2 (12 Kilifi + CBA). Symbiotic effectiveness was assessed (shoot biomass, SPAD index and N uptake). Nodule occupancy of 13 simultaneously co-inoculated strains in each experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
(83 reference statements)
0
8
0
1
Order By: Relevance
“…Even though theory would support the assumption that intercropping would result in more activity due to the interaction of roots, the proximity between companion crops could have resulted to less activity based on the results obtained in this study. An increase in the phosphatase activity on sole cropping indicated the high soil phosphorus in the rhizosphere of the cowpea crop (Table 2), which could be required for the cellular biosynthesis of adenosine triphosphate, necessary for the reduction of N 2 to NH 3 by the nitrogenase in the cowpea root nodules [38].…”
Section: Discussionmentioning
confidence: 99%
“…Even though theory would support the assumption that intercropping would result in more activity due to the interaction of roots, the proximity between companion crops could have resulted to less activity based on the results obtained in this study. An increase in the phosphatase activity on sole cropping indicated the high soil phosphorus in the rhizosphere of the cowpea crop (Table 2), which could be required for the cellular biosynthesis of adenosine triphosphate, necessary for the reduction of N 2 to NH 3 by the nitrogenase in the cowpea root nodules [38].…”
Section: Discussionmentioning
confidence: 99%
“…Proxies of strain fitness from singlestrain assays (e.g. nodule number) are rarely predictive of nodule occupancy in mixed-inoculation experiments (Mellor et al, 1987), and industrial inoculated strains are often outcompeted by rhizobia indigenous to agricultural fields (Box 2; Ndungu et al, 2018). Rates of nodule occupancy can be altered by deleting genes involved in biofilm formation and motility (Caetano-Anolles et al, 1988;Frederix et al, 2014), altering the copy number of an rRNA operon that influences growth rate (Cherni & Petit, 2019), and modifying the presence of plasmids (Crook et al, 2012) [Correction added after online publication 8 August 2019: the order of the last two reference citations in this sentence was transposed].…”
Section: New Phytologistmentioning
confidence: 99%
“…Most assays of rhizobial adaptation are conducted with single strains of bacteria. However, in soils, several rhizobial genera and scores of strains coexist in a single location (Graham, 2008;Rangin et al, 2008;Ndungu et al, 2018). Here, I review techniques to measure relative rhizobial fitness and provide an overview of our current understanding of rhizobial adaptation to the soil, the rhizosphere and nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the native rhizobial community that is often the most competitive for nodule occupancy tends to exhibit low N 2 fixation rates (for example see A.A. Cardoso et al 2017;Chibeba et al 2017). Indeed, for decades the failure of rhizobia to improve crop yields has often been attributed to the poor competitive abilities of the inoculant and not to poor N 2 fixation abilities (Triplett and Sadowsky 1992;Streeter 1994;Ndungu et al 2018). In strong support of this, it has been observed that the natural transfer of symbiotic islands from inoculant Mesorhizobium strains to the native Mesorhizobium population often, and rapidly, results in highly competitive strains with poor N 2 fixation capabilities (Sullivan et al 1995;Nandasena et al 2007).…”
Section: Synthetic Biology Approaches To Engineering the Symbiosismentioning
confidence: 99%